Caffeic Acid Phenethyl Ester as a DHODH Inhibitor and Its Synergistic Anticancer Properties in Combination with 5-Fluorouracil in a Breast Cancer Cell Line - Amalia E; Diantini A; Endang Prabandari E; Waluyo D; Subarnas A (Dove Medical Press, 2022)
Eri Amalia,1- 3 Ajeng Diantini,1 Erwahyuni Endang Prabandari,4 Danang Waluyo,4 Anas Subarnas1 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2Department of Pharmacology, Faculty of Science and Technology, Department of Pharmacy, Muhammadiyah University, Bandung, Indonesia; 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 4Research Center for Vaccine and Drug, National Research and Innovation Agency, Bogor, IndonesiaCorrespondence: Eri Amalia, Department of Pharmaceutics and Pharmaceutical Technology, Laboratory Building 1, Faculty of Pharmacy, Universitas Padjadjaran. Jl. Raya Bandung-Sumedang km.21. Jatinangor, West Java, 45363, Indonesia, Email amalia_eri@yahoo.co.id; amalia@unpad.ac.idIntroduction: A combination of chemotherapy agents is the best choice in breast cancer treatment to increase the patient survival rate. 5-fluorouracil (5-FU) is one of the drugs applied in combination with other drugs to control and delay development of cancer cells. Nevertheless, the occurrence of multidrug resistance and dose-limiting cytotoxicity have limited the efficacy of 5-FU treatment. Therefore, the discovery of new anti-breast cancer drugs should be pursued.Objective: To study potency of a promising naturally derived compound, caffeic acid phenethyl ester (CAPE), for breast cancer treatment in single and combination with 5-FU.Methods: Cytotoxicity of CAPE, 5-FU, and 5-FU+CAPE was studied by in vitro MTT experiment in MCF-7 cell line, and RT-PCR analysis was used to evaluate the change in gene expression due to the treatment. Moreover, an enzymatic assay and molecular docking analysis were applied to evaluate the possible mechanism of substance-induced apoptosis.Results: The study revealed that a single treatment of CAPE showed cytotoxicity with IC50 6.6 ± 1.0 μM and 6.5 ± 2.9 μM at 24 h and 48 h, respectively. Meanwhile, 5-FU showed cytostatic activity. The 5-FU + CAPE has a synergistic effect at 24 h treatment with a CI = 0.5 and an additive effect at 48 h treatment with CI = 1.0. CAPE was also found to enhances the mRNA expression of caspase-8 and BAX within 6 hours in combination with 5-FU compared to 5-FU treatment alone. Our study reveals a new mechanism of CAPE which is related to the inhibition of human dihydroorotate dehydrogenase (HsDHODH) with an IC50 of 120.7 ± 6.8 μM, by bound to the ubiquinone-binding site of the enzyme and could be responsible for inducing extrinsic and intrinsic apoptosis.Conclusion: This study demonstrated the cytotoxicity of CAPE potential to induce apoptosis of breast cancer MCF-7 cell line single and cytotoxic-cytostatic combination with 5-FU. Therefore, further studies to develop CAPE and its derivatives will be required to discover new candidates for breast cancer agents.Keywords: caffeic acid phenethyl ester, 5-fluorouracil, dihydroorotate dehydrogenase, DHODH, MCF-7, breast cancer